Food science and technology - edited by Geoffrey Campbell-Platt (Wiley-Blackwell,IUFoST, 2009)
This brand new comprehensive text and reference book is designed to cover all the essential elements of food science and technology, including all core aspects of major food science and technology degree programs being taught worldwide. Food Science and Technology, supported by the International Union of Food Science and Technology comprises 21 chapters, carefully written in a user-friendly style by 30 eminent industry experts, teachers and researchers from across the world. All authors are recognised experts in their respective fields, and together represent some of the world's leading universities and international food science and technology organisations